UBERIZAÇÃO, ENTRE A INOVAÇÃO E A DESIGUALDADE: UMA ANÁLISE RACIALIZADA ACERCA DO FENÔMENO DE PLATAFORMIZAÇÃO DO TRABALHO (REMUNOM, 2025)
Due to the impacts of globalization, the emergence of new forms of work organization, service provision, and the consolidation of the uberization model in the national context, this article aims to analyze how uberization influences the racialization of labor, fostering precariousness and subalternity, as well as reproducing significant socioeconomic inequalities. The methodology employed was bibliographic research, primarily through consulting articles from the CAPES Journal Portal, accessed via the Federated Academic Community (CAFe) of the Univerdade Federal Rural do Semi-Árido (UFERSA) and the SciELO Portal. Furthermore, the article is divided into sections: first, it addresses the phenomenon of platform economy and uberization; next, it examines the precariousness and subalternization of uberized labor. Finally, it explores how this context contributes to the perpetuation of resource inequality and the allocation of Black workers—the primary labor force in this sector—to jobs characterized by higher informality, confining them to positions of subservience as a reflection of "modern servitude."